Piceatannol Attenuates Testosterone-Induced Benign Prostatic Hyperplasia in Rats by Modulation of Nrf2/HO-1/NFκB Axis - Eid, Basma G.; Abdel-Naim, Ashraf B. (Frontiers in Pharmacology, 2020)
Benign prostatic hyperplasia (BPH) is a serious illness affecting middle-aged and elderly male patients. It is a complication of several diseases including metabolic syndrome. BPH has been associated with inflammation and increased oxidative stress in prostatic tissues. Piceatannol (PIC) is an active natural polyhydroxylated stilbene found in many plants. It has profound anti-inflammatory as well as antioxidant activities. However, it suffers relatively poor pharmacokinetic properties. Nanoformulation is an acknowledged approach to improve PIC bioavailability. The goal was to evaluate the ability of PIC in preventing testosterone-induced benign prostatic hyperplasia in rats. PIC was prepared in a self-nanoemulsifying drug delivery system (SNEDDS). Animals were placed into 7 groups: 1) control (vehicle), 2) PIC SNEDDS (20 mg/kg), 3) testosterone (3 mg/kg), 4) testosterone + PIC SNEDDS (5 mg/kg), 5) testosterone + PIC (10 mg/kg), 6) testosterone + PIC SNEDDS (20 mg/kg) and 7) testosterone + finasteride (5 mg/kg). Testosterone was injected SC while PIC SNEDDS and finasteride were given orally. All treatments were given once daily, 5 days / week for 4 consecutive weeks. PIC administration ameliorated increased prostate weights and indices in addition to histopathological alterations. Further it inhibited accumulation of lipid peroxidation, depletion of glutathione (GSH) and exhaustion of catalase (CAT). PIC SNEDDS exhibited anti-proliferative activities as demonstrated by the inhibition of cyclin D1 protein expression and Bcl2 mRNA expression in addition to enhancement of Bax mRNA expression and caspase-3 content. Immunohistochemically, PIC SNEDDS protected against the testosterone-induced increased expression of tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), nuclear factor kappa B (NFκB) and also offered protection against the decline in Nrf2 expression. Further, a significant enhancement of Nfe212 and Homx1 mRNA expression was detected in PIC SNEDDS-treated animals in comparison to the testosterone group. Conclusively, PIC prepared in SNEDDS protects against experimentally induced BPH via modulation of, at least partly, Nrf2/HO-1/ NFκB axis.